1987
DOI: 10.1161/01.hyp.9.3.230
|View full text |Cite
|
Sign up to set email alerts
|

Increased basal and thrombin-induced free calcium in platelets of essential hypertensive patients.

Abstract: SUMMARY Intracellular free calcium, [Ca 2 + ],, was studied in platelets of essential hypertensive subjects and normotensive controls under basal conditions and after stimulation with epinephrine, norepinephrine, angiotensin II, ouabain, and thrombin, using the fluorescent calcium indicator quin 2. Basal [Ca 2+ ], was significantly higher in hypertensive subjects (n = 32) than in normotensive controls (n = 30; 167.4 ± 5.0 vs 143.2 ± 3.1 nmol/L; p<0.001). Epinephrine, norepinephrine, angiotensin II, and ouaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 29 publications
(25 reference statements)
3
18
0
Order By: Relevance
“…In the present study, the basal [Ca 2ϩ ] i in platelets was elevated in hypertensive subjects, confirming most previous results (5,8,11,16,30). However, there was a considerable overlap in distribution between hypertensives and normotensives.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the basal [Ca 2ϩ ] i in platelets was elevated in hypertensive subjects, confirming most previous results (5,8,11,16,30). However, there was a considerable overlap in distribution between hypertensives and normotensives.…”
Section: Discussionsupporting
confidence: 92%
“…Platelets are often used in the study of cellular cation metabolism in hypertension, because they are readily available for study and are thought to share a number of features with vascular smooth muscle cells (20). Most investigators have reported that basal levels of cytosolic free Ca 2ϩ concentration ([Ca 2ϩ ] i ) are higher in human subjects with essential hypertension than in normotensive subjects (5,8,11,16,30) …”
mentioning
confidence: 99%
“…This issue is supported by the lack of a significant effect of ouabain on [Ca 2+ ], when added in vitro to our preparation of renal proximal tubules (see Figure 3). This finding is in agreement with other studies in cultured renal epithelial cells, 22 -47 toad urinary bladder, 28 and platelets, 48 although contrary evidence has been presented in renal cells. 49 The lack of effect of ouabain on [Ca 2+ ], in our preparation of renal proximal tubules is in contrast with the marked increase caused by removal of external Na + (J. Llibre, C. Gutterman, and D.C. Batlle, unpublished observation, 1988 50 and strophanthidin, another cardiotonic steroid, has been shown to increase contractile tension in small rings of rat aorta, suggesting increased Ca 2+ delivery to the contractile apparatus.…”
Section: Discussionsupporting
confidence: 93%
“…A large body of evidence has indicated that [Ca 2+ ], levels in platelet or other blood cells are increased in SHR and hypertensive patients. 2 - 5 However, whether [Ca 2+ ], in VSMC is increased in genetic hypertension is controversial. 6 ' pared with age-matched normotensive Wistar-Kyoto (WKY) rats.…”
Section: T He Cytosolic Free Calcium Concentration ([Camentioning
confidence: 99%